2019
DOI: 10.1007/s42452-019-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gelation behavior of PPC-based electrolyte on electrochemical performance of solid state lithium battery

Abstract: Polypropylene carbonate (PPC)-based solid state electrolyte was fabricated by using a cellulose membrane as a skeleton. The gelation behavior of the PPC-based solid electrolytes in solid-state lithium batteries was found, and the effect of this behavior on battery performance was studied. It was found that the solute lithium salt in the matrix greatly promoted the gelation of the PPC-based solid electrolyte under heating conditions upon contact with metallic lithium. This behavior allows the room temperature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…In fact, it is found that only when lithium metal is used is the measured conductivity high, whereas the commonly used stainless steel blocking electrode does not reproduce such results. Recently, the same group found that PPC is prone to decomposition upon heating with lithium metal and tends to form low molecular weight polymers or even PC monomers, which could serve as plasticizers, , and therefore, the surprisingly high ion conductivity of PPC-based CPEs should be attributed to the small molecules that lead to actual GPEs. Such GPEs supported a solid LiFePO 4 /Li battery and delivered excellent rate capability (5 C) and superior cycling stability (95%) at ambient temperature.…”
Section: Composite Solid Electrolytesmentioning
confidence: 99%
“…In fact, it is found that only when lithium metal is used is the measured conductivity high, whereas the commonly used stainless steel blocking electrode does not reproduce such results. Recently, the same group found that PPC is prone to decomposition upon heating with lithium metal and tends to form low molecular weight polymers or even PC monomers, which could serve as plasticizers, , and therefore, the surprisingly high ion conductivity of PPC-based CPEs should be attributed to the small molecules that lead to actual GPEs. Such GPEs supported a solid LiFePO 4 /Li battery and delivered excellent rate capability (5 C) and superior cycling stability (95%) at ambient temperature.…”
Section: Composite Solid Electrolytesmentioning
confidence: 99%
“…The solid polymer electrolytes (SPEs) have attracted huge attention in the last four decades and now matured enough owing to their tremendous technological importance established in the development of flexible-type all-solid-state advanced ion-conducting devices (i.e., rechargeable batteries, fuel cells, supercapacitors, solar cells, sensors, and so forth) [1][2][3][4][5][6][7][8][9][10]. These materials are novel and advantageous over their liquid counterparts especially relevant to the battery applications because they have adequate ionic conductivity and numerous other fascinating features like wide operating temperature range, lightweight, good shelf life, high energy density, leakage-free, ease of preparation, the flexibility of miniaturization, reduced flammability, low toxicity, good stability during the charge-discharge cycles, as well as appreciable mechanical and thermal stabilities [2,4,[8][9][10]. So far, a variety of SPEs including nanocomposite SPEs (NSPEs), plasticized SPEs (PSPEs), and plasticized nanocomposite SPEs (PNSPEs) have been beautifully developed with stateof-the-art, and their technological significance has been greatly appreciated with breakthroughs in the energy storing devices (batteries and supercapacitors) [2, 3, 6-8, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a variety of SPEs including nanocomposite SPEs (NSPEs), plasticized SPEs (PSPEs), and plasticized nanocomposite SPEs (PNSPEs) have been beautifully developed with stateof-the-art, and their technological significance has been greatly appreciated with breakthroughs in the energy storing devices (batteries and supercapacitors) [2, 3, 6-8, 10, 11]. At the early stage of the development of solid-state electrolyte materials, they exhibited some drawbacks from the technology point of view and therefore tremendous efforts have been made in the last decade researches to overcome the drawbacks and are thoroughly addressed in several recent reviews [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation electrode potential is related to the Fermi level of a polymer electrolyte . Among common polymer electrolytes, those with carbonyl group are stable at moderately high voltage (e.g., 4–4.5 V vs Li + /Li), , but polymers with an ether group are widely accepted to be unstable above 4 V vs Li + /Li, such as PEO . Because PEO is widely studied, and it has been commercialized in 3 V Li/LiFePO 4 (LFP) batteries, addressing the interfacial stability between 4 V cathodes (e.g., NCM and LiCoO 2 /LCO) and PEO has the potential to enable practical 4 V solid-state batteries in the future.…”
mentioning
confidence: 99%